2015
DOI: 10.1007/s11910-015-0536-2
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Counterparts of Hyponatremia: Pathological Mechanisms and Clinical Manifestations

Abstract: Hyponatremia, defined as a serum sodium concentration <135 mEq/L, represents the most frequent electrolyte disorder in older hospitalized patients. Early recognition of hyponatremia is mandatory, since it represents an independent risk factor that increases hospital mortality by 40 %. Delayed correction of hyponatremia may worsen brain edema, resulting in different degrees of neural damage. However, an overly rapid correction of serum sodium levels can lead to osmotic demyelination syndrome (ODS), a dreadful n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…The mechanism seems to be cytotoxicity affecting para ventricular and supraoptic neurons [38] other reports showed that the reason for sodium low [39] the result also showed that the sodium levels were decreased with age and this was in agreement with other reports.…”
Section: -Sodiumsupporting
confidence: 91%
“…The mechanism seems to be cytotoxicity affecting para ventricular and supraoptic neurons [38] other reports showed that the reason for sodium low [39] the result also showed that the sodium levels were decreased with age and this was in agreement with other reports.…”
Section: -Sodiumsupporting
confidence: 91%
“…Because the brain is confined by the rigid skull, tissue expansion compresses blood vessels to cause deficits in cerebral circulation, and eventually leads to herniation of the brainstem. Milder reductions in blood Na + levels produce a variety of neurological symptoms – such as nausea, confusion, headaches, and hallucinations – and elevate the risk of death in co-morbid states [67, 162, 204]. …”
Section: Common and Unique Roles Of Vrac Within The Brainmentioning
confidence: 99%
“…Even small decreases of serum sodium are associated with increased probability for adverse outcomes (cognitive impairment, falls, osteoporosis and fractures) [3].Decreased serum sodium levels are occasionally observed in patients with diabetes mellitus and can be attributed to numerous underlying pathogenetic mechanisms (Table 1) [4,5].The direct measurement of serum osmolality (Posm) can differentiate between hypotonic hyponatremia (with decreased Posm) and hyponatremia associated with normal or even increased tonicity. In the latter case hyponatremia is usually due to the coexistent hyperglycemia [6].…”
mentioning
confidence: 99%
“…Even small decreases of serum sodium are associated with increased probability for adverse outcomes (cognitive impairment, falls, osteoporosis and fractures) [3].…”
mentioning
confidence: 99%